Rotor Unbalanced Magnetic Force in Flux-switching Permanent Magnet Machines Due to Static and Dynamic Eccentricity. Issue 3 (7th February 2016) - Li, Silong; Li, Yingjie; Sarlioglu, Bulent
Abstract: This article investigates the rotor unbalanced magnetic force characteristics of a 12-stator-slot 10-rotor-pole flux-switching permanent magnet machine due to both static and dynamic eccentricity. The equations for radial and tangential components of the unbalanced magnetic force on the rotor are formulated. The 2D finite-element analysis results for a baseline 10-kW 15, 000-rpm ferrite flux-switching permanent magnet machine show that both static and dynamic eccentricity will result in a significant amount of unbalanced magnetic force in the flux-switching permanent magnet machine even under the no-load condition. This article also shows that the direction of rotor unbalanced magnetic force due to static eccentricity is fixed, while the direction of rotor unbalanced magnetic force due to dynamic eccentricity is rotating. This research clearly reveals the influence of eccentricity on the performance of flux-switching permanent magnet machine, and facilitates further research on the vibration and acoustic noise analyses of flux-switching permanent magnet machines.